2018
DOI: 10.15575/jpi.v4i1.2095
|View full text |Cite
|
Sign up to set email alerts
|

Improving Quality of Islamic Education Through Community Based Education: Principal Engagement

Abstract: The emergence of a community-based education paradigm is triggered by a large flow of modernization and democratization. Education should be decentralized. Its implementation in schools should be collaborative and the principal has a big role in this program. Therefore, this study aims to examine the involvement or participation of the principal in improving the quality of community-based PAI (Pendidikan Agama Islam/Islamic Education) in junior high school. The data were collected through indepth interview, ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Similar results are also seen in research conducted by Ansari (2016) which states that the role of students in the distribution of animal sacrifice meat can foster religiosity and concern. Arbi (2018) in his research conclusion also revealed that the sacrificial worship program was able to increase the loyalty of teachers. The results of this study also agree with investigations conducted by Khan et al (2015) who also stated that religious factors greatly influenced respondents' decisions in Pakistan in performing animal sacrifice worship.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Similar results are also seen in research conducted by Ansari (2016) which states that the role of students in the distribution of animal sacrifice meat can foster religiosity and concern. Arbi (2018) in his research conclusion also revealed that the sacrificial worship program was able to increase the loyalty of teachers. The results of this study also agree with investigations conducted by Khan et al (2015) who also stated that religious factors greatly influenced respondents' decisions in Pakistan in performing animal sacrifice worship.…”
Section: Discussionmentioning
confidence: 91%
“…This study also found that the role of students in distributing sacrificial lamb not only fostered student religiosity but also fostered a caring attitude towards others. Arbi (2018) expressed the same opinion that the qurban animal payment program was able to improve the teachers' social piety competence in teaching. This research revealed that community-based learning education could improve the quality of Islamic religious education in schools.…”
Section: Introductionmentioning
confidence: 88%
“…The existence of a wellstructured curriculum does not appear to be sufficient, and substantial improvements are needed that lead to the professional development of Islamic religious education teachers. Several previous studies have recommended the importance of developing Islamic religious education teacher professional programs to produce teachers who are competent in many aspects of pedagogical and sustainable teacher professional development (for example, Alhashmi & Moussa-Inaty, 2021;Sahin, 2018), and this can be well realized if there is an optimization of the participation and role of policy makers in the field of Islamic religious education (Arbi, 2018).…”
Section: Introductionmentioning
confidence: 99%